Little Prayer Book, 1522, and A Simple Way to Pray, 1535 : The Annotated Luther Study Edition - Luther, Martin, 1483-1546 (Book collections on Project MUSE., 2017)
This volume provides two of Martin Luther's most significant writings on prayer. In Little Prayer Book (1522), Luther seeks to reform the theology and practice of prayer in clear and understandable language for all people by encouraging simple, direct prayer to God, who promises to hear the one who prays. Luther focuses on the Ten Commandments, Apostles' Creed, and Lord's Prayer, giving his treatment of prayer a catechetical feel that would later provide the structure of his catechisms. In A Simple Way to Pray (1535), Luther offers his barber and all other readers insights into his own prayer life. He organizes his comments around the seven petitions of the prayer Jesus taught to his disciples. He also uses the Ten Commandments and the Apostles' Creed as resources for prayer. He sets out to "kindle a fire in the heart" and increase the reader's eagerness for prayer. This volume is excerpted from The Annotated Luther series, volume 4 (Pastoral Writings). Each volume and selection in the series contains new introductions, extensive annotations, illustrations, and notes to help shed light on Luther's context and to interpret his writings for today.